The Influence of Social Media Marketing, Product Quality and Price on Purchase Intention - RAMDANI, Fadilah; ANISA, Desty Cristya; SAHARA, Sahara (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to examine the influence of social media marketing, product quality, and price on purchase intention among consumers of Elacof Apparel, a local fashion screen-printing brand based in Cirebon, Indonesia. The background of the study highlights a decline in Elacof’s sales, which may be associated with inconsistent digital promotion, mixed perceptions of product quality, and pricing mismatches. A quantitative approach was applied involving 91 respondents, selected through Slovin’s formula from a population of 1,026 consumers. Data were collected using structured questionnaires and interviews and analyzed through IBM SPSS 25 software. Findings indicate that social media marketing, product quality, and price have a positive and statistically significant influence on purchase intention—both individually and simultaneously. The regression model showed that these three variables jointly explained 39.2% of the variance in purchase intention. The study confirms that effective use of digital platforms, consistent product quality, and value-aligned pricing are key to enhancing consumer engagement and purchasing behavior. This research contributes to the literature on digital marketing and consumer behavior in the MSME fashion sector and provides practical insights for brand development. Future research is recommended to expand the model by including brand image, customer satisfaction, and perceived value.